Lived experiences of pre-service elementary teachers on blended learning - Ceniza, Krystal Marie; Cuesta, Jessica Marie; Gatab, William Mae; Loro, Rhonamie; Tagalog, Hanna Mae; Tagra, Dianne Lyn; Laurito, Mia; Kilat, Ronnel Victor; Rivera, Bysche; Valle, Lislee (Intelektual Pustaka Media Utama, 2026)
The primary purpose of this study was to determine: i) experiences; ii) various resources; iii) varied activities; iv) 21st-century skills acquisition; v) challenges experienced; and vi) solutions to the challenges of the pre-service elementary teachers in blended learning. The study employed qualitative research and utilized Straussian grounded theory as a research design to guide data collection and coding to identify emerging categories and generate theory. Purposive sampling was employed to select the ten pre-service elementary informants with experience with blended learning. In analyzing the data gathered, Strauss and Corbin’s coding methods, namely open, axial, and selective coding, were employed. The six themes were created based on the raw responses of informants, namely: i) varied online resources; ii) tangible learning materials; iii) varied learning activities; iv) acquired 21st-century skills; v) challenges of blended learning; and vi) addressing the challenges. A theory emerged, “magma theory”, which further strengthens the characterization of having “shared experiences”, as manifested by the pre-service elementary teachers in this blended learning. The primary findings of this study were that pre-service teachers can overcome challenges in blended learning with adequate support from tools. Furthermore, they can also improve their 21st-century skills through appropriate activities that contribute to lifelong learning.